Impact of High-Power and Very High-Power Short-Duration Radiofrequency Ablation on Procedure Characteristics and First-Pass Isolation During Pulmonary Vein Isolation - Salló, Zoltán; Perge, Péter; Balogi, Bernadett; Orbán, Gábor; Piros, Katalin; Herczeg, Szilvia; Nagy, Klaudia Vivien; Osztheimer, István; Ábrahám, Pál; Merkely, Béla; Gellér, László; Szegedi, Nándor (Frontiers in Cardiovascular Medicine, 2022)
Introduction: High-power short-duration (HPSD) radiofrequency ablation has been proposed to produce rapid and effective lesions for pulmonary vein isolation (PVI). We aimed to evaluate the procedural characteristics and the first-pass isolation (FPI) rate of HPSD and very high-power short-duration (vHPSD) ablation compared to the low-power long-duration (LPLD) ablation technique. Methods: 156 patients with atrial fibrillation (AF) were enrolled and assigned to LPLD, HPSD, or vHPSD PVI. The energy setting was 30W, 50W, and 90W in the LPLD, HPSD, and vHPSD groups, respectively. In the vHPSD group, 90W/4 s energy delivery was used in the QMODE+ setting. In the other groups, ablation index-guided applications were delivered with 30W (LPLD) or 50W (HPSD). Results: Bilateral PVI was achieved in all cases. Compared to the LPLD group, the HPSD and vHPSD groups had shorter procedure time (85 [75-101] min, 79 [65-91] min, and 70 [53-83] min), left atrial dwelling time (61 [55-70] min, 53 [41-56] min, and 45 [34-52] min), total RF time (1567 [1366-1761] sec, 1398 [1021-1711] sec, and 336 [247-386] sec), but higher bilateral FPI rate (57%, 78%, and 80%) (all p-values < 0.01). The use of HPSD (OR=2.72, 95% CI 1.15-6.44, p=0.023) and vHPSD (OR=2.90, 95% CI 1.24-6.44, p=0.014) ablation techniques were associated with a higher probability of bilateral FPI. The 9-month AF-recurrence rate was lower in case of HPSD and vHPSD compared to LPLD ablation (10%, 8%, and 36%, p=0.0001). Moreover, the presence of FPI was associated with a lower AF-recurrence rate at 9-month (OR=0.09, 95% CI 0.04-0.24, p=0.0001). Conclusion: Our prospective, observational cohort study showed that both HPSD and vHPSD RF ablation shortens procedure and RF time and results in a higher rate of FPI compared to LPLD ablation. Moreover, the use of HPSD and vHPSD ablation increased the acute and mid-term success rate. No safety concerns were raised for HPSD or vHPSD ablation in our study.